Isolation of Enteric Ganglia from the Myenteric Plexus of Adult Rats. (1995) - Jaeger, Christine B.
Abstract : Enteric neurons and glia cells were isolated from adult Sprague Dawley rats. A procedure is described using a combination of microdissection and mechanical dissociation after enzyme treatment which yields large numbers of cell clusters suitable for tissue culture and grafting into the injured spinal cord. Differentiated enteric ganglia remained viable for at least 5 days in vitro Cultured neurons expressed histochemical reactivity for acetylcholinesterase and nicotinamide adenine dinucleotide phosphate diaphorase. Nestin positive glia, which represented a population of non-myelinating enteric Schwann cells, could also be identified in cultures maintained 5 days or longer in vitro . The myenteric plexus of adult rats can provide a readily available source of neurons and Schwann cells for grafting to the central nervous system.